2023
DOI: 10.1136/bmjopen-2023-076219
|View full text |Cite
|
Sign up to set email alerts
|

Is disease activity associated with social support and psychological distress in Crohn’s disease patients? Results of a cross-sectional study in a Chinese hospital population

Mengting Huang,
Lei Tu,
Linxia Wu
et al.

Abstract: ObjectivesThis study aims to assess the relative of social support and psychological distress in disease activity among patients with Crohn’s disease (CD) in China, and explore whether sex moderates the relationship between disease activity and social support and psychological distress in CD.DesignOur study has a cross-sectional design.SettingThis was a single-centre study, which was conducted in Wuhan, China.ParticipantsA total of 184 patients with CD at Union Hospital, Tongji Medical College, Huazhong Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Moreover, patients with CD typically require lifelong medication, which seriously affects their quality of life and increases psychological distress. The previous studies have found that disease activity in CD patients is associated with psychological disorders ( Huang et al, 2023 ). Thus, the search for effective biomarker is essential for distinguishing the CD-A and CD-R to implementation of effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with CD typically require lifelong medication, which seriously affects their quality of life and increases psychological distress. The previous studies have found that disease activity in CD patients is associated with psychological disorders ( Huang et al, 2023 ). Thus, the search for effective biomarker is essential for distinguishing the CD-A and CD-R to implementation of effective interventions.…”
Section: Introductionmentioning
confidence: 99%